Role of the Storm Episode in Dracontius’ Orestis Tragoedia (v. 41–45) - Ivan M. Nikolsky (Studia Litterarum)
The paper deals with the storm episode (v. 41–45), which is the opening episode in the Tragedy of Orestes (Orestis Tragoedia) by Dracontius, in terms of affecting further narrative. Although it is a starting point in one of the most substantial and mature works of the Carthaginian poet, it has not yet been the subject of special interest by researchers and commentators. This paper attempts to close this gap. The episode’s significance is evident even at the most cursory acquaintance with the poem. Because of the storm, Agamemnon returns to Mycenae late, which gives his wife Clytemnestra and her lover Aegisthus the opportunity to plan a conspiracy and murder of the king. This is already followed by the central event, the revenge of Orestes, and a whole chain of tragic events. I try to prove that the storm is important not only from the plot point of view, but also from the compositional point of view, influencing the understanding of the arrangement of characters, and also has a significant symbolic meaning, serving as an allegory of both war and civil strife. In my opinion, the episode plays a crucial role in understanding the general sense of the poem, its connections with the rest of Dracontius’ work, and the previous literary tradition. It also allows us to discover the political context relevant to the time of the work creation (late 5th century).